JUSTIFICATION OF THE SHELF LIFE OF FERMENTED DAIRY PRODUCTS BASED ON GOAT’S MILK - Nadirova , S.; Sinyavskiy, Yu. (Eurasian Journal of Applied Biotechnology, 2023)
The article presents the results of studies on the number of survival of lactic acid bacteria, which determine the shelf life of fermented milk products during storage. The studies were carried out at the Department of Food Biotechnology of the Almaty Technological University, as well as in the laboratory of biotechnology of specialized products and dietary supplements of the Kazakh Academy of Nutrition. In the preparation of fermented milk products, a starter consisting of Streptococcus thermophilus, Lactobacillus bulgaricus and Lactobacillus fermentum 14 was used. Lactobacillus fermentum 14, as a probiotic, exhibits antagonistic properties, which helps to extend the shelf life and does not allow yeast and mold to grow in the final products. Lactobacillus bulgaricus, in turn, synthesizes a specific enzyme, peptidoglycan hydrolase, which is responsible for the hydrolysis of peptidoglycan which is an important component of the bacterial cell wall. When dairy products are enriched with biologically active substances of berry syrups Lactobacillus bulgaricus actively synthesizes extracellular polysaccharides, which improve the structure of the clot, increase stability and prevent syneresis. Streptococcus thermophilus is a mild curing thermophilic culture with a high degree of viscosity that promotes the formation of a good clot. Rosehip, hawthorn and mountain ash syrups, grape peel extract enriched fermented milk products with biologically active substances, which improved the growth and development of lactic acid microorganisms. The addition of phytofillers not only enhance the microscopic picture, but also improves the consistency and odors of the products.